PENGARUH MODEL PEMBELAJARAN KOOPERATIF TUTOR SEBAYA BERBANTUAN MEDIA AUDIO VISUAL TERHADAP AKTIVITAS BELAJAR DAN HASIL BELAJAR IPA SISWA KELAS V SD GUGUS V KECAMATAN KARANGASEM - Ni Nyoman Lisna Handayani (Purwadita : Jurnal Agama dan Budaya, 2019)
This study aims to determine the magnitude of the influence of cooperative learningmodel peer tutors assisted audio visual media on learning activities and learning outcomes ofscience. This research is a quasi-experimental study with the design of The Posttest-Only ControlGroupDesign.ThestudypopulationisallstudentsofclassVSDClusterVDistrictKarangasemconsistingof9classeswithapopulationof219students.Atotalof46studentswereselectedasasampledeterminedbygrouprandomsamplingtechnique.ThecollectedwerelearningactivitiesusingobservationsheetsandIPAlearningresultsusingmultiplechoicetests.DatawereanalyzedusingMANOVAwithSPSS16.00forwindows.Theresultsofthestudyshowedthat:Firstly,thelearningactivity between the students who followed the cooperative learning model of peertutor with audio visual aid was better than the students who followed the conventional learningmodel (F of 10.78 and Sig = 0,000; p <0.05). Second, the learning outcomes of science betweenstudents who followed the cooperative learning model of peer tutors with audio-visual aid werebetter than students who followed the conventional learning model (F of 13.94 and sig = 0,000;p <0.05). Thirdly, simultaneously learning activity and science learning outcomes among studentswho follow cooperative learning model of peer tutor with audio visual aid are better than studentsfollowing the conventional learning model (F value 26,98 is smaller than 0.05).